Risk of impaired cognition after prenatal exposure to psychotropic drugs. (31st May 2017) - Wibroe, M. A.; Mathiasen, R.; Pagsberg, A. K.; Uldall, P.
Abstract : Objective: Prenatal exposure to psychotropic drugs may affect the trajectories of brain development. In a register study, we investigated whether such exposure is associated with long‐term impaired cognitive abilities. Method: Individuals born in Denmark in 1995–2008 were included. As proxies for cognitive impairment, requiring special needs education, attending special needs school, diagnoses of neurological/mental disorder, missed final examinations, and low school grade average were used. We accounted for maternal confounders. Results: We identified 868 159 individuals of whom 13 983 (1.6%) were prenatally exposed. The adjusted odds ratio (OR) was 0.97[0.92–1.02] for requiring special needs education, 1.28[1.14–1.43] for attending special needs school, 1.32[1.20–1.46] for a neurological/mental disorder diagnosis, 1.37[1.22–1.54] for missing the final examinations, and 1.13[0.82–1.55] for obtaining a low school grade average. Exposure to psycholeptics (primarily antipsychotics and sedatives) was correlated with significantly increased risk for four outcomes. The highest was the risk of missing the primary school examinations (OR: 1.51[1.29–1.76]). The overall highest risk concerned the presence of a neurological/mental disorder after prenatal exposure to psychoanaleptics (primarily antidepressants) (OR: 1.86[1.24–2.78). Conclusion: Prenatal exposure to psychotropic drugs affects proxy outcomes of cognitive disabilities at school age. Exposure to psycholeptics carries the largest risk. The role of psychoanaleptics is currently unclear.